(untitled) (The International Journal for Scientific Research, 2025)
Objectives: This study aims to identify the attitudes of educational counselors towards the use of artificial intelligence (AI) in counseling and its relationship to perceived self-efficacy and future orientation in Palestine. Methodology: The study employes a descriptive correlational approach and a predictive methodology. Measures were taken to assess counselors’ attitudes towards the use of AI in counseling, their perceived self-efficacy, and their future orientation. A sample of 294 male and female educational counselors in Palestinian public schools was selected using convenience sampling. Results: The results show that counselors’ attitudes towards the use of AI in counseling were high, with an average of 3.57, indicating a positive attitude and acceptance of the idea of ​​integrating AI into counseling. The level of perceived self-efficacy among counselors is also high, with an average of 4.16, while their level of future orientation was high, with with an average of 3.81. The results show a positive correlation between counselors’ attitudes toward using artificial intelligence in counseling and their perceived self-efficacy. A positive correlation was also found between counselors’ attitudes toward using AI in counseling and their future orientation. Furthermore, perceived self-efficacy and future orientation together accounted for 18.5% of the variance in counselors’ attitudes toward using AI in counseling. Recommendations: The study recommends implementing the proposed supervisory program, which would support counselors in effectively adopting and using artificial intelligence.